The N-degron pathway mediates the autophagic degradation of cytosolic mitochondrial DNA during sterile innate immune responses - Chan Hoon Jung; Yoon Jee Lee; Eun Hye Cho; Gee Eun Lee; Sung Tae Kim; Ki Sa Sung; Daeho Kim; Dong Hyun Kim; Yeon Sung Son; Jin-Hyun Ahn; Dohyun Han; Yong Tae Kwon (Cell Reports)
Summary: The human body reacts to tissue damage by generating damage-associated molecular patterns (DAMPs) that activate sterile immune responses. To date, little is known about how DAMPs are removed to avoid excessive immune responses. Here, we show that proteasomal dysfunction induces the release of mitochondrial DNA (mtDNA) as a DAMP that activates the cyclic GMP-AMP synthase (cGAS)-stimulator of interferon gene (STING) pathway and is subsequently degraded through the N-degron pathway. In the resolution phase of sterile immune responses, DNA-dependent protein kinase (DNA-PK) senses cytosolic mtDNA and activates N-terminal (Nt-) arginylation by ATE1 R-transferases. The substrates of Nt-arginylation include the molecular chaperone BiP/GRP78 retrotranslocated from the endoplasmic reticulum (ER). R-BiP, the Nt-arginylated species of BiP, is associated with cytosolic mtDNA to accelerate its targeting to autophagic membranes for lysosomal degradation. Thus, cytosolic mtDNA activates the N-degron pathway to facilitate its own degradation and form a negative feedback loop, by which the cell can turn off sterile immune responses at the right time.